Endoscopic ultrasound guided fine needle aspiration versus endoscopic ultrasound guided fine needle biopsy in sampling pancreatic masses: A meta-analysis. Issue 28 (July 2017) - Wang, Jing; Zhao, Shulei; Chen, Yong; Jia, Ruzhen; Zhang, Xiaohua
Abstract: Background: The comparison between endoscopic ultrasound guided fine needle aspiration (EUS-FNA) and endoscopic ultrasound guided fine needle biopsy (EUS-FNB) for the diagnosis of pancreatic masses is still controversial. Many factors can affect the final results. Methods: Databases, such as PubMed, EMBASE, Cochrane Library, and Science Citation Index updated from 2000 to 2016 were searched to include eligible articles. In the meta-analysis, the main outcome measurements were the diagnostic accuracy, number of needle passes, specimen adequacy, the rate of complications, and technical success. Results: Eight randomized controlled trials (RCTs) were identified, and a total of 921 cases were included in the meta-analysis. The diagnostic accuracy was not significantly different between the FNA and FNB groups. The specimen adequacy was higher in the FNB group compared with the FNA group. The number of needle passes to obtain sufficient tissue was lower in the FNB group. The rate of adverse events and technical success did not significantly differ between the 2 groups. But, the forest plot showed a trend toward lower technical success rate and a trend toward higher diagnostic accuracy in the FNB group, compared with FNA. Conclusion: We provide the evidence that FNB is comparable to FNA in terms of diagnostic accuracy, adverse events, and technical success. FNB gives higher specimen adequacy than that of FNA, despite performance of fewer needle passes.